Levels of anxiety in players of the lower categories - Castro Sánchez, M.; Zurita Ortega, F.; Chacón Cuberos, R.; Padial Ruz, R.; Martínez Martínez, A. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2018)
Due to the relationship between psychological variables and sports performance, sports psychology has gained special relevance in recent decades, so the present research aims to analyze the levels of anxiety in players of lower categories, using a Descriptive cross-sectional design on a sample of 156 teenage soccer players. For the collection of data, an ad-hoc questionnaire was used to record the sociodemographic variables and the Stai-Trait to measure anxiety levels. The results of this research indicate that six out of ten players show average levels of anxiety-state and three out of ten high, in terms of trait-anxiety, half have high anxiety and the other half. The main conclusion of this research is that the level of studies of footballers is related to levels of anxiety.